TRIGGERED: could refocused cell signaling be key to natural killer cell-based HIV immunotherapeutics?. (2nd February 2021) - Sugawara, Sho; Manickam, Cordelia; Reeves, R. Keith
Abstract : N/A: Natural killer (NK) cells are one of the critical innate immune effector cells that directly kill tumors and virus-infected cells, and modulate other immune cells including dendritic cells, CD4 + and CD8 + T cells. Signals from activating and inhibitory surface receptors orchestrate the regulatory and cytotoxic functions of NK cells. Although a number of surface receptors are involved, multiple signaling molecules are shared so that NK cell responses are synergistically regulated. Many pathogens and tumors evade NK cell responses by targeting NK cell signaling. Particularly in HIV/simian immunodeficiency virus (SIV) infection, the NK cell repertoire is diminished by changes in subsets of NK cells, expression of activating and inhibitory receptors, and intracellular signaling molecules. However, in-depth studies on intracellular signaling in NK cells in HIV/SIV infections remain limited. Checkpoint blockade and chimeric antigen receptor (CAR)-NK cells have demonstrated enhanced NK cell activities against tumors and viral infections. In addition, targeting intracellular signaling molecules by small molecules could also improve NK cell responses towards HIV/SIV infection in vivo . Therefore, further understanding of NK cell signaling including identification of key signaling molecules is crucial to maximize the efficacy of NK cell-based treatments. Herein, we review the current state of the literature and outline potential future avenues where optimized NK cells could be utilized in HIV-1 cure strategies and other immunotherapeutics in PLWH.